INNOVATION OF SUBJECTS TECHNICAL MECHANICS AND HYDRAULICS USING THE RELATION TO MATHEMATICS - RIHOVA, Dana; KOTASKOVA, Pavla; MARKOVA, Jana (Trends in education, 2013)
This paper deals with the use of mathematics in the subjects Technical mechanics and Hydraulics. Study texts were created. They demonstrate the relationship between both subjects and mathematics using the discussed issues. Necessary mathematical tools are commented at the level of the basic course.
Keywords: technical mechanics; hydraulics; mathematics